Pendampingan Masyarakat Adat Kurau dalam Optimalisasi Mahar sebagai Aturan Nafkah Harian: Model Pemberdayaan Berbasis Nilai-Nilai Syariah dan Hukum Adat - Hasan, Ahmadi; Zubaidah, Dwi Arini (JPM: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to enhance the understanding and skills of the Kurau Indigenous community in managing mahr (dowry) as a household economic instrument grounded in Sharia and customary law values. The main issue identified is the community’s perception of mahr merely as a ceremonial symbol in marriage, lacking a continuous function in family sustenance. The activity was conducted on Wednesday, August 13, 2028, at the Kurau Community Hall, involving 35 lecturers from the Faculty of Sharia at UIN Antasari, 40 community members, local officials, and representatives of the Office of Religious Affairs (KUA). The implementation consisted of four stages: (1) initial identification through surveys and interviews; (2) training and Focus Group Discussion (FGD) led by Prof. Ahmadi Hasan, M.Hum., and Dwi Arini Zubaidah, M.H.; (3) field counseling and simulation of mahr management; and (4) participatory evaluation using questionnaires and interviews. The results indicate a significant increase in participants’ understanding—from 22.5% before the program to 90% afterward—along with a shift from symbolic to functional interpretation of mahr. Participants expressed high satisfaction with the interactive and locally contextual methods. The program produced a training module, documentation video, and a local guidebook titled “Mahr and Daily Sustenance Based on Kurau Customary Law.” It is recommended to establish a Kurau Mahr and Sustenance Working Group to sustain and expand the program’s impact.